Pemahaman Tugas Malaikat Perspektif Surat Ar Ra’d Ayat 11 Dan Implikasinya Terhadap Kehidupan Di Era Modern - Azdania, Hanifa; Nurrohim, Ahmad; Nugroho, Kharis; Azizah, Alfiyatul; Mahmud, Abdullah (Institut Agama Islam Sumatera Barat Pariaman, 2024)
Angels are servants of Allah who are obedient in carrying out worship. Many Muslims are not yet aware of the importance of the role of angels in influencing daily life. This research aims to know and understand the duties of angels in Surah Ar Ra'd verse 11 and the implications for contemporary life. This research can be classified as a literature study, where data collection is carried out through reading, understanding and evaluating various references related to the topic qualitative research. The data collection method involves triangulation, with inductive data analysis. The author uses qualitative descriptive methods and content analysis, starting by explaining the general phenomenon regarding the duties of the angel Hafadzah in the Koran. Conclusions are drawn based on specific verses of the Qur'an and hadith. This research uses a data collection method involving the study of related literature which includes how angels function. Analysis is carried out through the synthesis of information from various sources to understand the relevance, effectiveness, research results show that the job of Angels in this verse is Angels who guard, all on the basis of Allah's orders. These angels are called Hafadzhah Angels. The implications of this research can contribute to knowledge of the Duties of Angels and a servant's faith in Angels related to faith and Implications for Life Contemporary.